Characterization of the Long-Term Impedance Variations Due to Electric Vehicle Charging From 20 kHz to 500 kHz - Jon Gonzalez-Ramos; Itziar Angulo; Igor Fernandez; Bernhard Grasel; Alexander Gallarreta; Amaia Arrinda; David de la Vega (IEEE Open Access Journal of Power and Energy)
This paper aims to empirically characterize the long-term grid impedance variations due to Electric Vehicle Charging Processes (EVCPs) in the frequency range from 20 kHz to 500 kHz. The study is supported by a measurement campaign performed in a controlled Low Voltage (LV) grid in Austria, composed of a Secondary Substation (SS) and four houses, which statistically represents the public LV grids in Austria. The results show that different impedance states (with different spectral patterns and amplitudes) can be identified during the charging processes of all the EVs under analysis. Additionally, time variability within each impedance state is also registered. The findings, which cover the still uncharacterized frequency band from 20 kHz to 500 kHz, have important implications for the performance of Narrowband Power Line Communications (NB-PLC), the propagation of Non-Intentional Emissions (NIEs) and the definition of a reference impedance in this frequency band.